2020
DOI: 10.18231/2455-1732.2018.0021
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study between conventional fistulectomy and SLOFT in cases of low fistula in ano

Abstract: Introduction: Fistula in ano is a common anorectal disorder requiring surgical intervention. It is associated with high recurrence rate and post-operative complications. In this study we have analysed and compare results of a newer technique for low anal fistula SLOFT with conventional Fistulectomy. Aims and Objective: To compare Submucosal Ligation of Fistula Tract (SLOFT) with conventional fistulectomy in patients of low anal fistula by analysing various intra-operative factors and post-operative outcome. Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…The overall weighted average operation time of sphincter-sparing procedures was 34.5 (19.0-52.5) minutes, with a weighted average postoperative hospital stay of 0.8 (0-1.5) days. Only 3 studies reported healing time [50,59,62]; the weighted average was 15.1 (7.7-28.0) days (Table 4). The morbidity rate was very low, with a total of 6 complications registered (Table 4).…”
Section: Perioperative Detailsmentioning
confidence: 99%
“…The overall weighted average operation time of sphincter-sparing procedures was 34.5 (19.0-52.5) minutes, with a weighted average postoperative hospital stay of 0.8 (0-1.5) days. Only 3 studies reported healing time [50,59,62]; the weighted average was 15.1 (7.7-28.0) days (Table 4). The morbidity rate was very low, with a total of 6 complications registered (Table 4).…”
Section: Perioperative Detailsmentioning
confidence: 99%